Occurrence of Oral Erasures and Metalinguistic Activities in two-way writing processes - Moura, Karolynne Kaya Maria Amorim (2023)
Considering that recent studies in the field of written language learning indicate the importance of metalinguistic comprehension in the development of reading and writing skills, associated with the teaching and learning practices of the mother tongue carried out at school, this study aims to analyze the occurrences of oral erasures and metalinguistic activities carried out by newly literate students during collaborative text production tasks. Linked to the studies of Textual Genetics, from a linguistic-enunciative approach, the dialogue between a pair of newly literate students when writing the same text was considered as a unit of analysis. For this, the methodological path was based on the audiovisual records of the dyad in the writing process, as well as the school manuscript resulting from this construction, preserving the entire atmosphere of the classroom. The productions of oral erasures associated with the metalinguistic activities performed by the children point out, in addition to the knowledge already established by the students in the teaching-learning process, as initial results, the knowledge that is being solidified in this process of teaching the mother tongue.